Localized abdominal wall metastasis of papillary renal cell carcinoma: a case report - Nahal, Chadi; Wunker, Claire; Keller, Jennifer (Frontiers in Surgery, 2024)
IntroductionPapillary renal cell carcinoma accounts for one tenth of all renal cell carcinomas. Compared to other renal cell carcinoma subtypes, it is more often localized at the time of diagnosis and rarely metastasizes to the skin. There are no previously reported cases of cutaneous papillary renal cell carcinoma localized to the abdominal wall which we present here.Case presentationA 77 year-old female with multiple previous cancers, including a stage 1 left papillary renal cell carcinoma, treated with partial nephrectomy 32 months prior to presentation, was found to have a left upper abdominal wall mass on interval screening computed tomography. Fine needle aspiration was performed, obtaining limited tissue, followed by incisional biopsy. Histology and immunohistochemistry were consistent with renal cell carcinoma. She underwent operative excision of the abdominal wall mass with reconstruction using mesh and left posterior rectus fascial release. Histology and immunohistochemistry of the operative specimen reconfirmed the diagnosis of cutaneous metastasis of renal cell carcinoma. She was treated with adjuvant pembrolizumab and has no existing evidence of disease.ConclusionsPapillary renal cell carcinoma metastasized to the skin is uncommon, especially when localized to the abdominal wall without any other sites of metastases. Metastasis should be on the differential diagnosis when evaluating newly identified abdominal masses in patients with a history of papillary renal cell carcinoma. When localized, abdominal wall metastasis of papillary renal cell carcinoma can be effectively treated with resection and reconstruction, followed by systemic therapy when indicated.